Comparison of GB-SAR Imaging Algorithms for a Landslide Monitoring Application - De La Cruz L. (2020)
A comparative analysis of three imaging algorithms for Ground Based Synthetic Aperture Radar (GB-SAR) systems has been conducted in order to select the most appropriate algorithm to be used in a landslide monitoring application. These algorithms are Frequency Domain Back Projection (FDBP), Range Migration Algorithm (RMA), and Discrete Linear Inverse Problem (DLIP). The comparison is based on image reconstruction quality, computational efficiency, and displacement measurement accuracy. Simulated and real data were used to test and compare the algorithms. Results show that FDBP is the most appropriate method for the proposed application. © 2020 IEEE.